The influence of parental involvement and social support on students’ career decision making - Renata, Farah; Rahma, Dian Dwi Nur (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
This study aims to: investigate the extent to which parental involvement and social support influence students’ skills of career decision making. A quantitative approach was employed, involving 121 participants from the 2022 cohort of the Faculty of Social and Political Sciences (FISIPOL) at X University, selected using a probability sampling technique. Data were collected using the scales for career decision making, parental involvement, and social support, analyzed using multiple regression analysis, and processed with SPSS version 25. The results of the study showed that: (1) there is a significant influence of parental involvement and social support on students’ career decision making skills; (2) there is no significant influence of parental involvement on students’ career decision making skills; and (3) there is a significantly positive influence of social support on students’ career decision making skills